2017
DOI: 10.1093/treephys/tpx131
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhizal type governs root exudation and nitrogen uptake of temperate tree species

Abstract: Even though the two dominant mycorrhizal associations of temperate tree species differentially couple carbon (C) and nitrogen (N) cycles in temperate forests, systematic differences between the biogeochemical cycles of arbuscular mycorrhizal (AM) and ectomycorrhizal (ECM) tree species remain poorly described. A classification according to the mycorrhizal type offers the chance, though, to develop a global frame concept for the prediction of temperate ecosystem responses to environmental change. Focusing on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 74 publications
2
62
0
Order By: Relevance
“…Microcosm studies suggest that AM trees exhibit relatively greater soil C input resulting in a stronger rhizosphere priming effect and hence more rapid soil C loss (Wurzburger & Brookshire, ). In a greenhouse experiment, EcM plant species and fungi but not AM systems enhance exudation in response to drought, which is probably an adaptation to secure microbial activity and continuous nutrition to plants (Liese et al ., ). The AM Rhizophagus intraradices releases mostly formiate, acetate and glucose (Toljander et al ., ), whereas EcM fungi and potentially ErM fungi exude large quantities of oxalate (van Schöll et al ., ; Fransson et al ., ).…”
Section: Soil Processesmentioning
confidence: 97%
See 1 more Smart Citation
“…Microcosm studies suggest that AM trees exhibit relatively greater soil C input resulting in a stronger rhizosphere priming effect and hence more rapid soil C loss (Wurzburger & Brookshire, ). In a greenhouse experiment, EcM plant species and fungi but not AM systems enhance exudation in response to drought, which is probably an adaptation to secure microbial activity and continuous nutrition to plants (Liese et al ., ). The AM Rhizophagus intraradices releases mostly formiate, acetate and glucose (Toljander et al ., ), whereas EcM fungi and potentially ErM fungi exude large quantities of oxalate (van Schöll et al ., ; Fransson et al ., ).…”
Section: Soil Processesmentioning
confidence: 97%
“…Mycorrhizal seedlings recover from drought stress better than non-mycorrhizal seedlings (Auge, 2001;Lehto & Zwiazek, 2011). EcM trees retain their photosynthesis to a greater extent compared to AM trees (Meier et al, 2016;Liese et al, 2018). However, severely water-limited systems (except Australian and Mediterranean semi-deserts) harbour AM but not EcM plants (Tedersoo, 2017), which may be related to the greater plasticity of AM hyphal production and withstanding highly negative water potentials (Querejeta, Egerton-Warburton & Allen, 2009;Vargas et al, 2010).…”
Section: (2) Water Stressmentioning
confidence: 99%
“…Consistent with the generally lower contribution of AM fungi than EM fungi to soil extracellular enzymes (Joner & Johansen, ; Phillips et al ., ), higher soil phosphomonoesterase and β‐glucosidase occurred in treatments where Salix clones had higher EM colonization relative to AM colonization (Baum et al ., ), and soils from around EM trees generally have higher enzyme activities than AM fungi‐colonized soils (Phillips et al ., ). A comparison of N uptake by four AM and four EM tree species under controlled conditions confirmed that the ratio of organic (supplied as an amino acid) to inorganic (nitrate + ammonium) taken up per unit root surface area was higher in EM species than in AM species (Liese et al ., ). AM trees accumulated six times more N from inorganic forms than EM trees did, independent of tree size, with no difference in uptake of N from amino acids.…”
Section: Nutritional Advantages Of Being Dualmentioning
confidence: 97%
“…ECM can be beneficial to plant productivity by enhancing plant growth or resistance to abiotic stress ( Alvarez-Lafuente et al, 2018 ). They also can improve water and nitrogen acquisition of the host plants and play a key role in the nutrition acquisition of forest trees ( Liese et al, 2018 ). The colonization of ECM induces higher soil porosities, which has been proven to play a crucial role in achieving success in black truffle plantations ( Alonso Ponce et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%